If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 + 4y + -8 = 17y + -14 + -5y Reorder the terms: 42 + -8 + 4y = 17y + -14 + -5y Combine like terms: 42 + -8 = 34 34 + 4y = 17y + -14 + -5y Reorder the terms: 34 + 4y = -14 + 17y + -5y Combine like terms: 17y + -5y = 12y 34 + 4y = -14 + 12y Solving 34 + 4y = -14 + 12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12y' to each side of the equation. 34 + 4y + -12y = -14 + 12y + -12y Combine like terms: 4y + -12y = -8y 34 + -8y = -14 + 12y + -12y Combine like terms: 12y + -12y = 0 34 + -8y = -14 + 0 34 + -8y = -14 Add '-34' to each side of the equation. 34 + -34 + -8y = -14 + -34 Combine like terms: 34 + -34 = 0 0 + -8y = -14 + -34 -8y = -14 + -34 Combine like terms: -14 + -34 = -48 -8y = -48 Divide each side by '-8'. y = 6 Simplifying y = 6
| 6n^2-18n-13=0 | | 4x^2-48x+5=0 | | 36x^2-684x-648=0 | | 60-6x=3x+22 | | 3+9x=34+x | | -2y(3+4)=8y+12 | | 9+6(x-5)+(3x-8)=9x-29 | | 5s+4+s=-20 | | (3x+2)7=5x+2 | | y=3-3x | | (x-3)(3x+7)=0 | | y^2+9y+18= | | 13-8x=45-22x | | -32-9x=9x+22 | | 91-4x=2x+19 | | y=x^2-16 | | y=3X^2 | | 7x-13=5(x-3) | | 3x^2-9x=8 | | x^2+2x+8=0 | | x^2-5-6=0 | | 2(2e+5)= | | (2x-5)(x+5)-2x*x=75 | | 5w-4v=-6 | | 7q+9=26 | | 9f+4=112 | | 8p-9=71 | | 4a+12=6[a-(5-a)] | | 6x^2-30=36 | | 2x+14=26 | | 3g-12=51 | | 8f+9=23 |